Anaphylaxis after ingestion of dust mite (Dermatophagoides farinae)-contaminated food: A case report - P. Rangkakulnuwat (2020)
© 2020, Malaysian Society for Parasitology. All rights reserved. Domestic mites have been recognized as the most common allergen responsible for respiratory allergy. Herein, we report a case of anaphylaxis due to ingestion of dust mitecontaminated food. A 14-year-old boy presented to the Emergency Department with chest discomfort, wheezing, eyelid angioedema, and urticarial rash twice in a month after eating meals, including tempura fried squids and onion fritters (containing wheat flour, eggs, squid, and onion). Anaphylaxis had been diagnosed and successfully treated. The investigations showed that the patient was sensitive to house dust mites. Positive skin prick-to-prick test response to incriminated flour and negative tests to wheat allergen extract and uncontaminated flour were demonstrated. The microscopic analysis of causative cooking flour identified the presence of Dermatophagoides farinae. During the oral food challenge test, the patient was able to eat tempura-fried squids and onion fritters, made with uncontaminated flour, without any adverse reaction. Hence, oral ingestion of dust mite-contaminated food was the culprit of this severe allergic reaction.